Henry Holiday : his stained-glass windows for gilded-age New York - Bryant, George (Northern lights, 2023)
Henry Holiday (1839-1927) was a polymath who counted figures such as Lewis Carroll, William Morris, Edward Burne-Jones and Emmeline Pankhurst as his friends. Most significantly, he was unquestionably one of the greatest stained-glass artists of the Victorian-Edwardian period, yet his considerable achievements have not received the recognition that they deserve. Taking Holiday's commissions for New York State churches as its focus, George Bryant's ground-breaking study places the artist's transatlantic accomplishments in the context of the social, artistic, religious and economic shifts that shaped his success in the US during America's Gilded Age - a period where existing social hierarchies were challenged by new money and European immigration that ended with the outbreak of the First World War. Also providing a clear understanding of the technical and aesthetic differences that set Holiday's stained glass apart from that of his contemporaries such as Edward Burne-Jones, La Farge, and Tiffany, Bryant's truly original publication, based on substantial archival research, makes a significant contribution to our understanding of nineteenth-century stained-glass design and Henry Holiday's important achievements